2019
DOI: 10.1111/jocn.14967
|View full text |Cite
|
Sign up to set email alerts
|

Pressure injury prevalence and predictors among older adults in the first 36 hours of hospitalisation

Abstract: Aims and objective To describe the prevalence and predictors of pressure injuries among older adults with limited mobility, within the first 36 hr of their hospital admission in Australia. Background Pressure injuries are significant health, safety and quality of care issues for patients and healthcare organisations. The early implementation of the recommended pressure injury prevention international clinical practice guidelines is a way to reduce hospital‐acquired pressure injuries. There is a paucity of evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 35 publications
5
49
0
2
Order By: Relevance
“…Nosso estudo apresenta limitações, primeiramente não avaliamos a interação entre diversas comorbidades, já que literatura aponta um impacto maior no risco para LP quando várias comorbidades estão associadas (Liu et al, 2019). Um estudo realizado em junho de 2019 encontrou que idade e o número de comorbidades é fator preditivo para LP entre pessoas com idade ≥65 anos com mobilidade limitada (Latimer et al, 2019). Em segundo lugar, temos um desenho de estudo que, por ser um corte transversal, não nos permite fazer fortes inferências sobre causa e efeito.…”
Section: Discussionunclassified
“…Nosso estudo apresenta limitações, primeiramente não avaliamos a interação entre diversas comorbidades, já que literatura aponta um impacto maior no risco para LP quando várias comorbidades estão associadas (Liu et al, 2019). Um estudo realizado em junho de 2019 encontrou que idade e o número de comorbidades é fator preditivo para LP entre pessoas com idade ≥65 anos com mobilidade limitada (Latimer et al, 2019). Em segundo lugar, temos um desenho de estudo que, por ser um corte transversal, não nos permite fazer fortes inferências sobre causa e efeito.…”
Section: Discussionunclassified
“…Regrettably, while a large number of studies on the prevalence and incidence of HAPI have been published, only a few studies considered the prevalence and characteristics of patients presenting CAPI at hospital admission, so this should be considered a vital research field (Latimer et al, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…A complete skin inspection and a PI risk assessment are therefore recommended as soon as possible (and no later than eight hours) after hospital admission to identify and document the presence of PIs and implement appropriate interventions (National Pressure Ulcer Advisory Panel et al, 2014). Regrettably, while a large number of studies on the prevalence and incidence of HAPI have been published, only a few studies considered the prevalence and characteristics of patients presenting CAPI at hospital admission, so this should be considered a vital research field (Latimer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have confirmed that older adults living in the community become more vulnerable to developing PI with increasing age and multiple comorbidities. 5 However, current research on PI has mainly focused on the hospital setting, and research examining the presence of PI before hospitalization, known as community-acquired PI (CAPI), has been limited. 6 In addition, researchers have found that environmental factors are related to the occurrence of PI.…”
Section: Introductionmentioning
confidence: 99%